IMPLEMENTASI TAHUN INFRASTRUKTUR DI PROVINSI JAWA TENGAH - Suwantho Adhi (Politika: Jurnal Ilmu Politik, 2017)
Year of infrastructure is the Central Java Provincial Government’s policy since 2014 which is expected to improve the condition of infrastructure, particularly roads. Through qualitative method, this research focused on the meaning of infrastructure year and its impact.The result showed that the year of the infrastructure is the policy of increasing budget allocations for rehabilitation and construction of roads through budget of Central Java. The result of the policy is better roads conditions. The success of the infrastructure year was supported by the commitment of parliaments in budgeting process and ability of local governments to implement all activities. Keywords : Policy, Implementation, Infrastructure